METHODOLOGICAL BASIS FOR THE FUTURE ENGINEERS’ PROFESSIONAL MOBILITY FORMATION - Olga Vitalievna Lyubimova (Вестник Северо-Кавказского федерального университета)
This article is devoted to the question of future engineers’ professional mobility formation. Different approaches to the notion of future engineers’ professional mobility are distinguished.